Hubungan Dukungan Suami terhadap Sikap Ibu dalam Melakukan Imunisasi Bayi di Puskesmas Gebang, Jalan Jenderal Sudirman No. 104, Kecamatan Gebang, Kabupaten Langkat Tahun 2022 - Lismaretni Lorenta; Ester Simanullang; Mediana, Mediana (PPNI UNIMMAN, 2025)
Every baby is expected to receive five complete basic immunizations. Complete basic immunization coverage is the percentage of babies aged 0-11 months who have received five complete basic immunizations according to the number and time of basic immunization. This study aims to find the relationship between husband's support as an independent variable and the mother's attitude in infant immunization as a dependent variable, each of which data is collected at the same time. The sample in this study were 45 babies registered at the Gebang Health Center, Langkat Regency for May to July 2021, with the research sample method being total sampling. This research was conducted at the Gebang Health Center, Langkat Regency. From the results of the study, there is a significant relationship between husband's support and the mother's attitude in providing infant immunization in the Gebang Health Center work area, Jl.Jendral Sudirman No.104 Langkat. The correlation strength (r) is 0.730, indicating the relationship between the two variables in the strong degree category. The direction of the positive correlation (+) indicates that the greater the husband's support, the more positive the mother's attitude in providing infant immunization. The results and discussion of the study are expected to be a reference for nursing students in: Conducting further research on factors that can influence mothers' attitudes in providing infant immunization.